Komparasi Kurikulum Madrasah Ibtidaiyah dan Sekolah Dasar dalam Pembentukan Karakter Religius Peserta Didik - Khairullah Khairullah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the comparison between the curriculum of Madrasah Ibtidaiyah (MI) and Elementary Schools (SD) in shaping students' religious character. A qualitative approach with a descriptive method was employed to explore in depth the differences and similarities of the two curricula, particularly in the aspects of religious values integrated into the learning process. Data were collected through in-depth interviews, observations, and curriculum document analysis from several MIs and SDs in Banjarmasin.The findings reveal that the MI curriculum focuses more on strengthening Islamic education through specialized subjects such as Al-Qur'an, Hadith, Fiqh, and Akhlak, as well as integrating religious values into general subjects. Meanwhile, the SD curriculum positions Islamic education as part of the subject